Pain Pleasure Principle in Joy Harjo s Poetry: The Foundation of Personal Choices and Identity - Mohanad Ghanim Glayl (English Education Postgraduate Program, Universitas Negeri Manado, 2024)
This article examines Joy Harjo journey the renowned poet and musician has navigated a tumultuous life filled with pain and adversity The pain pleasure principle is a fundamental aspect of human decision making Beliefs values actions and decisions are all shaped by this principle but it is crucial to examine them critically through a postcolonial lens to better understand the power dynamics and social structures that influence our interpretation of pain and pleasure A lot of studies have been conducted on Indigenous literature but very little has delved into the exploration of pain and pleasure specifically in the works of Joy Harjo However the current study argues that when examining Indigenous literature it is essential to approach it through the lens of post colonial theory and consider concepts such as identity hegemony and hybridity in order to fully understand the hidden motives behind these literary works In her literature Harjo s poetry serves as a testament to the transformative nature of language and its ability to heal Harjo s work particularly her book Conflict Resolution for Holy Beings emphasizes the importance of language in bridging cultural and linguistic gaps Joy Harjo literature reflects the pleasure serves as a driving force in our lives motivating us to make certain choices and take specific actions These choices and actions in turn shape our individuality and help us develop a unique identity The study stresses on Pain pleasure principle that plays a crucial role in Indian American literature particularly evident in the works of Joy Harjo< em>< p>